Evaluating the Efficacy of a Special Education Advocacy Training Program. Issue 4 (28th October 2016) - Burke, Meghan M.; Goldman, Samantha E.; Hart, Melanie S.; Hodapp, Robert M.
Abstract: Increasingly, parents are relying on advocates to ensure that children with disabilities receive appropriate educational services. As agencies begin to train advocates to work with families, it is necessary to evaluate the efficacy of such advocacy training programs. This study evaluated the efficacy of the Volunteer Advocacy Project (VAP), a 40‐h training workshop that has been delivered since 2008 to six cohorts live and via webcasts. The aim of the study was to determine whether the VAP increased the knowledge and advocacy skills of its trainees and how trainee and training characteristics related to the effectiveness of the training. This study examined changes from pretest to posttest knowledge and advocacy skills of 90 trainees of the VAP. We also examined interactions between pre/post change and trainee and training characteristics. Participants demonstrated significant gains from pre‐ to posttests in their knowledge of special education and in their advocacy skills. Those participants who partook of the training in latter cohorts and at distance sites showed more progress in special education knowledge. Increases in advocacy skills differed by type of participant: compared to parent participants, professionals demonstrated significantly greater pre/post test increases in advocacy skills. This study has important implications for researchers, practitioners, and policymakers.